2015
DOI: 10.1007/s00394-015-1042-7
|View full text |Cite
|
Sign up to set email alerts
|

The effects of coenzyme Q10 administration on glucose homeostasis parameters, lipid profiles, biomarkers of inflammation and oxidative stress in patients with metabolic syndrome

Abstract: www.irct.ir : IRCT201502245623N35.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 31 publications
7
66
0
4
Order By: Relevance
“…This study indicated that CoQ10 supplementation in subjects with PCOS for 12 weeks resulted in significant reductions in FPG, serum insulin, HOMA‐IR and HOMA‐B and a significant increase in QUICKI compared with the placebo. We have previously demonstrated that supplementation with 100 mg/day CoQ10 among subjects with MetS for 8 weeks had beneficial effects on markers of insulin metabolism . In addition, 200 mg/day CoQ10 supplementation in patients with T2DM for 12 weeks led to a significant improvement in glycaemic control .…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…This study indicated that CoQ10 supplementation in subjects with PCOS for 12 weeks resulted in significant reductions in FPG, serum insulin, HOMA‐IR and HOMA‐B and a significant increase in QUICKI compared with the placebo. We have previously demonstrated that supplementation with 100 mg/day CoQ10 among subjects with MetS for 8 weeks had beneficial effects on markers of insulin metabolism . In addition, 200 mg/day CoQ10 supplementation in patients with T2DM for 12 weeks led to a significant improvement in glycaemic control .…”
Section: Discussionmentioning
confidence: 95%
“…Previously, the beneficial effects of CoQ10 supplementation on metabolic profiles among subjects without PCOS have been evaluated. We have shown that the intake of 100 mg/day CoQ10 supplements among subjects with MetS for 8 weeks had beneficial effects on markers of insulin metabolism . In addition, a significant improvement in glycaemic control was seen following the supplementation of 200 mg/day CoQ10 in patients with T2DM for 12 weeks .…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…CoQ10 is widely used as a dietary supplement and the oral doses of CoQ10 in human up to 1200 mg d −1 are reported to be safe . In our clinical trial with dyslipidemic patients, the dosage of CoQ10 supplementation (total of 120 mg d −1 ) was chosen based on previous clinical studies, and consistent with other studies …”
Section: Methodsmentioning
confidence: 99%
“…15 In overweight or obese patients with type 2 diabetes, supplementation with CoQ10 (200 mg/day for 3 months) significantly reduced HbA1c levels (mean baseline HbA1c reduced by 0.7%) and decreased weight and waist circumference. 16 The question arises as to how CoQ10 might directly influence glycaemic homeostasis.…”
Section: Coenzyme Q10 (Coq10)mentioning
confidence: 99%